The Use Of Learning Media In Physical Education Learning Sports And Health During The Covid-19 Pandemic In State Vocational High Schools In Bekasi City - Cahyono, Taufik Tri; Resita, Citra; Hidayat, Abdul Salam; Gemael, Qorry Armen (Jurnal MensSana, 2023)
This study aims to find out how high the level of use of learning media in learning PJOK during the pandemic covid-19 in vocational high schools in bekasi city. This study uses descriptive quantitative methods. The method used in this study is the survey method with instruments in the form of questionnaires. The subjects in this study were PJOK Teachers at State Vocational High Schools in Bekasi City which numbered 27 people. The data analysis techniques in this study use quantitative descriptive analysis presented in the form of percentages. The results of this study showed that the level of use of learning media in PJOK learning during the covid-19 pandemic at State Vocational High Schools in Bekasi City was in the "very low" category of 3.70% (1 teacher), "low" at 33.3 3% (9 teachers), "sufficient" by 25.93% (7 teachers), "high" by 37.04% (10 teachers), and "very high" by 0.00% (0 teachers). Based on the average score, which is 18.48 is in the category of enough with a frequency of 7 teachers.